Reference values for right ventricular volumes and ejection fraction with real-time three-dimensional echocardiography: evaluation in a large series of normal subjects - Tamborini, Gloria; Marsan, Nina Ajmone; Gripari, Paola; Maffessanti, Francesco; Brusoni, Denise; Muratori, Manuela; Caiani, Enrico G; Fiorentini, Cesare; Pepi, Mauro (Journal of the American Society of Echocardiography, 2010)
The quantification of right ventricular (RV) size and function is of diagnostic and prognostic importance. Recently, new software for the analysis of RV geometry using three-dimensional (3D) echocardiographic images has been validated. The aim of this study was to provide normal reference values for RV volumes and function using this technique. A total of 245 subjects, including 15 to 20 subjects for each gender and age decile, were studied. Dedicated 3D acquisitions of the right ventricle were obtained in all subjects. The mean RV end-diastolic and end-systolic volumes were 49 +/- 10 and 16 +/- 6 mL/m2 respectively, and the mean RV ejection fraction was 67 +/- 8%. Significant correlations were observed between RV parameters and body surface area. Normalized RV volumes were significantly correlated with age and gender. RV ejection fractions were lower in men, but differences across age deciles were not evident. The current study provides normal reference values for RV volumes and function that may be useful for the identification of clinical abnormalities.